User motive factors: the rudiments to email satisfactory communication - Anumudu, Chinedu Eugenia; Megat Al Imran Yasin,; Akmar Hayati Ahmad Ghazali,; Syed Agil Alsagoff, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Our study aims to evaluate if user motive factors, comprising; cognitive needs, social integrative needs, and personal integrative needs might influence email satisfactory communication among South-East Nigerian academic staff. The study was proposed because empirical evidence has proven these user motive factors as effective elements of the uses and gratification theory; capable of influencing satisfactory communication on other virtual communication media. However, past studies appeared little or no consideration has been explicitly given towards integrating them on email interaction related-study to attest them. Therefore, this study was conducted via a quantitative research method because it required hypotheses testing to infer the outcomes and generalize them to the targeted population. Regarding the key findings of the study, it showed that South-East Nigerian academic staff email usage patterns differed from one another. However, the salient email usage pattern established that almost the majority of them mostly prefer using their email addresses to the official ones. Furthermore, the direct effects relationships demonstrated that only two dimensions of user motive construct had significant direct effects on email satisfactory communication. Whilst the social integrative needs had no significant direct effects. Nonetheless, personal integrative needs contributed most to email satisfactory communication. Conclusively, it is recommended that South-East Nigerian academic staff and other email users should mostly consider personal integrative needs and cognitive needs if they intend to achieve email satisfactory communication. The outcomes of our study further contributed to the virtual media satisfactory communication domain, especially the asynchronous ones.